The effect of service quality and room prices on guest satisfaction of Rangkayo Basa Hotel - Riko Hidayat; Irdha Yusra (Marketing Management Studies, 2021)
This study aims to determine, The Influence of Tangibles, Reliability, Responsiveness, Assurance, Empathy, and Price on Customer Satisfaction at Rangkayo Basa Hotel. The type of research used is quantitative research. The population in this study were all guests staying at the Rangkayo Basa Hotel. The sampling technique used in this study was probability sampling, while the sample was taken as many as 150 people. Data was collected through questionnaires and then analyzed descriptively and Independent-Sample T-Test with program SPSS version 16. The results showed that the variables of Reliability, Responsiveness, Empathy, Price are the main factors that determine high or low customer satisfaction. While the Tangibles variable, Assurance has a not too dominant contribution to customer satisfaction.